INTERACTION OF ISLAMIC BANKING SECTOR WITH INDONESIAN ECONOMIC GROWTH FOR 2000-2010 - Mukhlis, Imam (UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
This paper aims to analyze the dinamics interaction of islamic banking sector with Indonesian economic growth for 2000-2010. The methode of analyze used in this research is granger causality and Vector Error Correction Model (VECM). Besides that we use stationary test to chek wether the data have unit root or not. We use time series data of total islamic bank fnancing, fxed invesstment, trade and gross domestic product. We found that in the short run there is evidence of bidirectional relationship between fnancing of islamic bank, fxed investment, trade and economi growth. Where as in the long run there is relationship between islamic banking with economic growth on Indonesian economy. To improve the role of islamic banking on Indonesian economy, Bank Indonesia must push islamic banking to expand their activity on riil sector and rural area.Keywords: Islamic Banking sector, Financial Intermediary, Economic Growth, Vector Error Corrrection Model